2017
DOI: 10.1080/01919512.2017.1326005
|View full text |Cite
|
Sign up to set email alerts
|

Towards a New Oxidation Process Using Ozone to Regenerate Coked Catalysts

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. ABSTRACTThis work focuses on the regeneration of a zeolite catalyst from industry deactivated by fouling with coke. To replace high temperature combustion, a common and energy intensive process, an oxidation process under milder conditions (50°C-200°C) has been investigated using ozone. Coked zeolite has been oxidized by an ozone stream in a fixed bed reactor, and regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The most common technique used for this measure is the N 2 adsorption and desorption experiment. Comparison of results for a fresh and deactivated catalyst emphasizes the direct impact of carbon deposition on the catalyst surface area and pore characteristics [149]. During the catalytic pyrolysis of PE in a conical-spouted bed reactor carried out by Elordi et al with different zeolites, coke deposition led to the reduction of the BET surface area, 19% and 39% for HZSM-5 and HY zeolites, respectively, as well as the micropore area [71].…”
Section: Structural and Physical Propertiesmentioning
confidence: 98%
See 3 more Smart Citations
“…The most common technique used for this measure is the N 2 adsorption and desorption experiment. Comparison of results for a fresh and deactivated catalyst emphasizes the direct impact of carbon deposition on the catalyst surface area and pore characteristics [149]. During the catalytic pyrolysis of PE in a conical-spouted bed reactor carried out by Elordi et al with different zeolites, coke deposition led to the reduction of the BET surface area, 19% and 39% for HZSM-5 and HY zeolites, respectively, as well as the micropore area [71].…”
Section: Structural and Physical Propertiesmentioning
confidence: 98%
“…Khangkham et al reported the apparition of a plateau after 2 h, suggesting that coke removal is not complete [148]. Richard et al also found that a maximum of 74.3% of coke could be removed from deactivated catalyst after 6.5 h [149]. This observation is explained by the diffusion limitations due to the instability of the created oxidizing species, causing their rapid degradation before they reach the unreacted coke surface.…”
Section: Ozonationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, they observed that coke removal with O2 starts on the metal sites, while that with O3 starts on the alumina support [63]. Furthermore, temperatures higher than 150 °C were not beneficial due to the strong diffusion constraints of O3 inside the zeolite particles, decomposing O3 rapidly [64]. Khangkham et al [65] investigated the regeneration of coked ZSM-5 after polymethyl methacrylate cracking, using O3 at low temperature.…”
Section: Ozone/oxynitride Oxidationmentioning
confidence: 99%